KEKUATAN MENGIKAT PERJANJIAN NOMINEE DALAM PENGUASAAN HAK MILIK ATAS TANAH - Sancaya, I Wayan Werasmana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 3 (2013)DO - 10.24843/JMHU.2013.v02.i03.p10, 2013)
Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 Nominee A g re e ment or tru s tee is a n a g re e ment that use a utho r i t y whi c h is used the n a me o f I ndo n e sian r e sidents n a me a nd the I ndon e sian r e sidents g ive p o w e r of a t t o r n e y to the fo re i g n e r to make them do a n le g a l a c t tow a rds their la n d. Nominee a g ree m e nt o f ten ca l l e d with r e p re s e ntation or b o r ro we d n a m e ,d e p e nd o n the letter of stat e ment or pow e r of a t t o r n e y that made b y both of the side, fo re i g n e r b o r r ow n a mes f r om I ndon e sian to be w r i t ten a s the land ’ s o wn e r on the c e rtifi ca t e , but then the I ndo n e sian d e p e nd on t he d e e d of d e c la ra t i on t h e y h a v e ma d e i g no r e t h a t the r ea l own e r of the l a nd a nd i t s autho r i z a t i on do or re p r e s e nted to that f o re i g n e r. The v a l i di t y a nd pow e r o f bind i ng the nom i n e e a g ree ment is ca n ’ t be s e p a r a ted f r om c lause 1320 a nd c lause 1338 K U HPe r d a t a . I f the nom i n e e a g re e m e nt a lr ea d y not i c e a ng ful f i l l the legit i mate r eg ui r e ment of the a g ree m e nt b a s e d on c lause 132 K U HPe r d a t a a nd b a s e d on 1338 K U HPe r d a ta, s o that nom i n e e a g ree m e nt a lr ea d y h a ve the bindi n g pow e r t o e v e r y sides. B a s e d on the p rin c ip l e of P ac ta S und S e rv a nd a , t h e a g re e ment that is made b y e v e r y sides, include n o m i n e e a g r ee ment h a s a bind i ng pow e r such a s l a w for them who h a ve ma d e i t .
Keywords: Binding Power, Nominee Agreement, Authorization, Land Rights